Negotiating Meaning and Aesthetic Effects: Figurative Language Distribution and Translation Patterns in Sapardi Djoko Damono’s Indonesian–Arabic Poetry - Yusuf Haikal (Asalibuna, 2026)
Figurative language plays a central role in constructing meaning and aesthetic effects in poetry, yet its translation across linguistic and cultural boundaries remains challenging. Studies on Indonesian–Arabic poetry translation, particularly Sapardi Djoko Damono’s works, are still limited. This study aims to analyze the distribution of figurative language and identify translation patterns in the Arabic translation of Hujan Bulan Juni (Hammuka Daimun). Employing a qualitative descriptive approach, the study analyzes 120 figurative language units identified from 33 poems translated into Arabic. The data were examined by comparing figurative expressions in the source and target texts and classifying their translation patterns. The findings reveal that personification, symbolism, and metaphor are the dominant figurative forms. Five translation patterns were identified: retention, transformation, reduction, recreation, and partial reduction. Retention is the most frequent pattern (99 data; 82.5%), followed by partial reduction (7), transformation (6), reduction (6), and recreation (2). These findings indicate that the translation of figurative language in Hammuka Daimun involves continuous negotiation between meaning and aesthetic effects, balancing the preservation of poetic imagery with adaptation to Arabic linguistic and literary conventions.   Abstrak:  Bahasa figuratif memiliki peran penting dalam membangun makna dan efek estetika dalam puisi, tetapi penerjemahannya lintas bahasa dan budaya menghadapi tantangan karena penerjemah harus melakukan negosiasi antara mempertahankan makna dan menjaga efek puitis. Kajian mengenai penerjemahan sastra Indonesia–Arab, khususnya penerjemahan puisi Sapardi Djoko Damono, masih terbatas. Penelitian ini bertujuan untuk menganalisis distribusi bahasa figuratif dan mengidentifikasi pola penerjemahan dalam puisi Hujan Bulan Juni karya Sapardi Djoko Damono yang diterjemahkan ke dalam bahasa Arab melalui Hammuka Daimun. Penelitian ini menggunakan pendekatan deskriptif kualitatif dengan data berupa 120-unit bahasa figuratif yang ditemukan dari 33 puisi dalam Hujan Bulan Juni. Data dianalisis melalui perbandingan ekspresi figuratif pada teks sumber dan teks sasaran serta klasifikasi pola penerjemahan. Hasil penelitian menunjukkan bahwa personifikasi, simbolisme, dan metafora merupakan bentuk bahasa figuratif yang dominan. Penelitian ini menemukan lima pola penerjemahan, yaitu retention, transformation, reduction, recreation, dan partial reduction. Retention menjadi pola yang paling dominan dengan 99 data (82,5%), diikuti oleh partial reduction (7 data), transformation (6 data), reduction (6 data), dan recreation (2 data). Temuan ini menunjukkan bahwa penerjemahan bahasa figuratif dalam Hammuka Daimun merupakan proses negosiasi makna dan efek estetika melalui upaya mempertahankan citra puitis sekaligus menyesuaikan ekspresi dengan konvensi bahasa dan sastra Arab.